793 A position paper on the future requirements for occupational health physicians in the public health service, ireland. (24th April 2018) - Sisson, L; Carolan, S
Abstract : Introduction: At a time when health resourcing costs are contracting, it is vital that services examine the potential to maximise the efficiency of their services and resources. The objective of workforce planning is to develop knowledge and intelligence data on the workforce, to inform decisions at local level and to drive improvements in Occupational Health service outcomes. Methods: The Workplace Health and Wellbeing Unit was set up in March 2016 under Priority 2 Staff Engagement within the Health Services People Strategy 2015–2018. [www.hse.ie]. With reference to the HSE People Strategy 2015–2018 'We have clearly defined workforce planning as a key component of our people' Occupational Health Services is one of four areas of governance and responsibility. A mapping exercise of current Occupational Health Physician establishments and a profiling of activity in the occupational health departments were conducted. A literature review of best practice in models of care was completed. An agreed framework for workforce planning was adhered to. Result: A position paper on The Future Requirements for Occupational Health Physicians in the Health Service, Ireland has been submitted to relevant decision makers. Regular review of the progression of this work will take place. Discussion: Occupational Health Services are reasonably well established in the Irish health care setting, however the future of the services have never been defined using a planned approach at national level As such this is the first initiative to identify and calculate the requirements for the future that ensure a sustainable future for the specialty and the service. The position paper presented information on current Occupational Health Physician Staffing Establishments in the Irish Health Service, and it proposes a model of care for future delivery of Occupational Health Services provision in the Health Service in Ireland, and finally it articulates WHWU'S approach to maximise Occupational Health Physician roles in the context of workforce planning within the service.